IMPLEMENTASI PELAYANAN PERNIKAHAN DI PANDEMI COVID-19 PERSPEKTIF MASHLAHAH MURSALAH (STUDI KASUS DI KUA KECAMATAN LAWANG) - Syahrul Permana; Khoirul Asfiyak; Dwi Ari Kurniawati (Jurnal Hikmatina, 2022)
KUA, Lawang District, Malang Regency, by implementing provisions regarding marriage service procedures, which only received a response from the people of Lawang District, Malang Regency, there was acceptance and rejection of these provisions, the refusal was due to the limitation of the number of attendees who participated in the marriage contract process and the necessity to include negative documents for Antigen Swab, the public The reason is that KUA, Lawang District, Malang Regency makes it difficult for people to register marriages.This study uses a qualitative approach and the type of research used is empirical juridical. In using descriptive methods, researchers can study and understand the state and condition of an object through proper interpretation through interview, observation and documentation techniques. The results of the first study were the procedures for marriage services during the Covid-19 pandemic at the KUA, Lawang District, Malang Regency, in accordance with the Circular of the Director General of Islamic Community Guidance No. P-001/DJ/HK.III.007/07/2021. While the results of the second study of marriage services in the Covid-19 pandemic at KUA, Lawang District, Malang Regency, the perspective of mashlahah murslah aims as a form of maintaining a number of foundations for the welfare of mankind, especially in Indonesia through providing protection for them to fulfill the purpose of fulfilling hifzu din (maintaining religion), hifzu nafsi. (guarding the soul), hifzu aqli (maintaining reason) which is included in the main maqasid ash-shari'ah.  Kata kunci: Implementation, Wedding During a Pandemic, Mashlahah Mursalah